Contribution of intraoperative electrical stimulations in surgery of low grade gliomas: a comparative study between two series without (1985–96) and with (1996–2003) functional mapping in the same institution. Issue 6 (16th May 2005) - Duffau, H; Lopes, M; Arthuis, F; Bitar, A; Sichez, J-P; Van Effenterre, R; Capelle, L
Abstract : Objectives: Despite the growing use of intraoperative functional mapping in supratentorial low grade glioma (LGG) surgery, few studies have compared series of patients operated on without and with direct electrical stimulation (DES) by the same team. The present study compared the rate of LGG surgery performed in eloquent areas, the rate of postoperative sequelae, and the quality of resection during two consecutive periods in the same department—the first without and the second with the use of intraoperative electrophysiology. Methods: Between 1985 and 1996, 100 patients harbouring a supratentorial LGG underwent surgery with no functional mapping (S1). Between 1996 and 2003, 122 patients were operated on in the same department for a supratentorial LGG using intraoperative cortico-subcortical DES (S2). Results: Comparison between the two series showed that 35% of LGGs were operated on in eloquent areas in S1 versus 62% in S2 (p<0.0001), with 17% severe permanent deficits in S1 versus 6.5% in S2 (p<0.019). On postoperative MRI, 37% of resections were subtotal and 6% total in S1 versus 50.8% and 25.4%, respectively, in S2 (p<0.001). In both groups, survival was significantly related to the quality of resection. Conclusions: The results of the present study allow, for the first time, quantification of the contribution of intraoperative DES in LGG resection. Indeed, the use of this method leads to the extension of indications of LGG surgery within eloquent areas; to a decrease in the risk of sequelae; and to improvement of the quality of tumour resection, with an impact on survival.